World Drug Report 2005 - United Nations Office on Drugs; Crime (United Nations, 2005)
The World Drug Report 2005 provides one of the most comprehensive overviews of illicit drug trends at the international level. In addition, this year it presents the work of UNODC in two new areas of research: an estimate of the financial value of the world drug market, and the preliminary steps towards the creation of an illicit drug index. The analysis of trends, some going back 10 years or more, is presented in Volume 1. Detailed statistics are presented in Volume 2. Taken together these volumes provide the most up to date view of today’s illicit drug situation.